MILESTONES IN THE EVOLUTION OF CULTURAL MARKETING AND CURRENT CHALLENGES - Elena-Lavinia (PĂTRAȘCU) CIUCULESCU; Florin-Alexandru LUCA (Management Intercultural, 2022)

(untitled)
Cultural marketing evolved from a set of techniques borrowed from the commercial sector to a relationship-based marketing. This translates into an original, bespoke, and meaningful cultural experience provided to the consumer, while staying true to the objectives advocated by each cultural organization. This article is a literature review aimed at highlighting key phases in the development of marketing in the arts and the cultural events sector. Additionally, the paper analyses some of the challenges that cultural organizations face amidst recent social, economic, and political developments worldwide, such as the Covid-19 pandemic, the aging of the population, or the integration of technology, to name a few. Monitoring these phenomena and adapting marketing strategies to confront the effects of major changes is crucial to the survival and development of cultural entities.